DAMPAK STRATEGIC THINKING TERHADAP KUALITAS HIDUP STUDI MAHASISWA - Katarina Leba; Balthasar Watunglawar (LPPM Politeknik Saint Paul Sorong, 2020)
The purpose of this study is to describe and analyze the form of strategic thinking and study life, the impact of strategic thinking on study life, and the factors that affect the quality of studies life. For achieving those objectives, this study using qualitative research methods. The data obtained through questioners and documentation techniques reduced, analyzed, and concluded. The research found that many students weak in thinking strategically. Students’ study life often was not arranged regularly. They were sometimes irrational in thinking and act. Many of them lost orientation and did not realize their essential task. Many students were not discipline and tend to relax, affected on hedonistic lifestyle, easily affected, and lose in value. To improve the quality of study life, students have to increase strategic thinking ability, think rationally and analytically before doing everything. The impact of a good study life (which has gone through a strategic thought process) is a change in behavior. Factors that influence the life of studies such as the campus with the system and regulations, teachers, and learning support facilities must be taken seriously for an educational revolution and strategic quality. The findings of this research are expected to be useful for next researchers in the field of management, accounting, administration and economics.